A Few Pseudomonas Oligotypes Dominate in the Meat and Dairy Processing Environment - Stellato, Giuseppina; Utter, Daniel R.; Voorhis, Andy; De Angelis, Maria; Eren, A. Murat; Ercolini, Danilo (Frontiers in Microbiology, 2017)
The occurrence of bacteria in the food processing environments plays a key role in food contamination and development of spoilage. Species of the genus Pseudomonas are recognized as major food spoilers and the capability to actually determine spoilage can be species- as well as strain-dependent. In order to improve the taxonomic resolution of 16S rRNA gene amplicons, in this study we used oligotyping to investigate the diversity of Pseudomonas populations in meat and dairy processing environments. Sequences of the V1-V3 regions from previous studies were used, including environmental swabs and food samples from both meat and dairy processing plants. We showed that the most frequently found oligotypes belonged to P. fragi and P. fluorescens, that the most abundant oligotypes co-occurred, and were shared between the meat and dairy datasets. All the oligotypes occurring in foods were also identified in the environmental samples of the corresponding plants, highlighting the important role of the environment as a source of strains for food contamination. Oligotypes of the same species showed different levels depending on food processing and type of sample, suggesting that different strains of the same species can have different adaptation efficiency, leading to resilient bacterial associations.